Thermal Nondestructive Testing of Composite and Metal Parts Manufactured by Additive Technologies; Russian Journal of Nondestructive Testing; Vol. 58, iss. 11 - Chulkov A. O. Arseniy Olegovich; Vavilov V. P. Vladimir Platonovich; Kladov D. Dmitry; Yurkina V. A. Varvara Alexandrovna (2022, 2022)
Title screen